Screening, identification and fermentation conditions optimization of agricultural antibiotic-producing bacteria - QIN Baoshan, LIANG Liyun, HE Haiyan, LI Yanting, FU Yue, QIN Yongling (Zhongguo niangzao)
The agricultural antibiotic-producing strain was screened from soil by dilution coating plate method using Gaoshi No.1 medium supplemented with potassium dichromate, and identified by morphological observation, physiological and biochemical experiments, and molecular biological technique. The fermentation conditions of the screened strain were optimized through single factor and response surface tests based on the diameter of the inhibition zone against Fusarium chlamydosporum as the response value. The results showed that a strain of agricultural antibiotic-producing strain Ly was screened and identified as Methylobacterium oryzae, which exhibited good antibacterial activity against F. chlamydosporum, Aspergillus aculeatu and Escherichia coli with inhibition zone diameters of 23.11 mm, 12.13 mm, and 6.80 mm, respectively. The optimal fermentation conditions for producing agricultural antibiotics by M. oryzae Ly were liquid loading volume 100 ml/250 ml, soybean cake powder as nitrogen source, fermentation temperature 31 ℃, rotation speed 220 r/min, initial pH 8, and fermentation time 7 d. Under these optimal conditions, the inhibition zone diameter of M. oryzae Ly against F. chlamydosporum was 41.91 mm, which was 1.81 times larger than that before optimization.